n = 1 ∑ 2 0 1 1 ( ( n 2 + n ) ( n + 1 ) ! n 2 + n + 1 )
If the above summation can be stated in the form of a ! − b ! a ! − b ! − 1 , find a + b.
Thanks to Math man - title taken from math man's problem - This is hard
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
( n 2 + n ) ( n + 1 ) n 2 + n + 1 = n × n ! 1 − ( n + 1 ) × ( n + 1 ) ! 1 Σ n = 1 2 0 1 1 ( n 2 + n ) ( n + 1 ) n 2 + n + 1 = 2 0 1 3 ! − 2 0 1 2 ! 2 0 1 3 ! − 2 0 1 2 ! − 1 a + b = 4 0 2 5
Problem Loading...
Note Loading...
Set Loading...
simplify as: = = = ( n 2 + n ) ∗ ( n + 1 ) ! n 2 + n + 1 n ∗ ( n + 1 ) 2 ∗ n ! ( n + 1 ) 2 − n ∗ ( n + 1 ) ∗ ( n + 1 ) ! n n ∗ n ! 1 − ( n + 1 ) ∗ ( n + 1 ) ! 1 hence n = 1 ∑ 2 0 1 1 ( ( n 2 + n ) ∗ ( n + 1 ) ! n 2 + n + 1 ) = n = 1 ∑ 2 0 1 1 ( n ∗ n ! 1 ) − n = 1 ∑ 2 0 1 1 ( ( n + 1 ) ∗ ( n + 1 ) ! 1 ) = n = 1 ∑ 2 0 1 1 ( n ∗ n ! 1 ) − n = 2 ∑ 2 0 1 2 ( n ∗ n ! 1 ) we see that all terms except last and first cancels out,hence n = 1 ∑ 2 0 1 1 ( ( n 2 + n ) ∗ ( n + 1 ) ! n 2 + n + 1 ) = 1 ∗ 1 ! 1 − 2 0 1 2 ∗ 2 0 1 2 ! 1 = 2 0 1 2 ∗ 2 0 1 2 ! 2 0 1 2 ∗ 2 0 1 2 ! − 1 comparing the question a ! − b ! = 2 0 1 2 ∗ 2 0 1 2 ! note that ( n + 1 ) ! − n ! = n ! ( n + 1 − 1 ) = n ∗ n ! hence 2 0 1 3 ! − 2 0 1 2 ! = 2 0 1 2 ∗ 2 0 1 2 ! and 2 0 1 2 + 2 0 1 3 = 4 0 2 5